P4_2 Earth’s Toilet Trouble - Morris, Owen William; Banks, Lewis Jefferey; Laird, Aaron James; Morris, Liam Stuart (Physics Special Topics, 2021)
How large a radius would a toilet bowl need to have in order to cause the Earth to stop rotating? In this paper, a circular motion model of the common flush toilet is explored. By keeping the height of the flush constant and calculating the mass of the water for every possible radius; we have calculated that the toilet bowl would need to have a radius of 4.65 × 10^8 m. For this scenario to occur, the motion of the flush would need to be in a clockwise direction when located on the North Pole to cause the Earth to cease rotating on its axis.